Impact of population aging on economic growth, health care expenditure and labor productivity in Malaysia - Abd Rahman, Siti Wardah (2018)
Malaysia is aging a a rapid speed but at a lower level of development. The aging process is expected to accelerate in the future. Obviously, it raises the question of how population aging affect the Malaysian economy. Therefore, the first issue is on determining whether population aging will boost economic growth. The second issue highlighted in this study is related to the impact of population aging on health care expenditure. The third issue addressed in this study is about the impact of population aging on labor productivity. In respond to these issues, this study underline three objectives. To answer the three objectives, Autoregressive Distributed Lag (ARDL) model is run using time-series data in the span of 15 to 35 years, in order to study the long-run and short-run impact. The main findings for the first objective showed that the declining fertility rate retards economic growth, as well as old-age dependency ratio and population aged 65+ give negative but insignificant impact on economic growth for the first objective. This imply that aging will inhibit economic growth in the long run, due to increasing dependency ratio. For the second objective, the main findings revealed that higher population aged 65+ raises private health expenditure. This implies aging significantly pushes up health spending in private healthcare sector in the long run. For the third objective, the main findings showed that the older workers give negative but insignificant impact on total labor productivity and they give positive but insignificant impact on labor productivity in services sector. However, the middleaged workers give a positive and significant impact on total labor productivity and labor productivity in agriculture and manufacturing sectors. These imply that aging is not found to boost the total labor productivity and labor productivity by sector in the long run. Therefore, we can conclude that the findings bring to light that aging can be a burden to the economy. Malaysia needs to be more prepared for bigger population of senior citizens that will increase faster.